2019
DOI: 10.1002/bjs.11185
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes and long-term quality of life after total pancreatectomy

Abstract: Background Total pancreatectomy is required to treat diseases involving the entire pancreas, and is characterized by high morbidity rates and impaired long‐term quality of life (QoL). To date, risk factors associated with perioperative and long‐term outcomes have not been determined fully. Methods Data from patients undergoing total pancreatectomy between 2000 and 2014 at two high‐volume centres were analysed retrospectively to assess risk factors for major surgical complications. Short Form (SF) 36, European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 32 publications
9
64
1
Order By: Relevance
“…7 However, in a series describing 12-year results of 2 very high-volume centers, 30-day and 90-day mortality rates were lower with 2% and 3%, respectively. 6 These results are in line with the results from the United States and Sweden, which both had an in-hospital mortality of 2%, yet are in contrast with the high mortality rates in both Germany (10%) and the Netherlands (11%). The difference in mortality rates is interesting, and, next to age 75 and vascular resection, country was identified as a predictor.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7 However, in a series describing 12-year results of 2 very high-volume centers, 30-day and 90-day mortality rates were lower with 2% and 3%, respectively. 6 These results are in line with the results from the United States and Sweden, which both had an in-hospital mortality of 2%, yet are in contrast with the high mortality rates in both Germany (10%) and the Netherlands (11%). The difference in mortality rates is interesting, and, next to age 75 and vascular resection, country was identified as a predictor.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study with 329 patients from 2 very high-volume centers reported a low 30-day mortality of 2.1% after TP. 6 In contrast, a recent pan-European snapshot study reported an inhospital mortality of 5% after TP. 7 The latter study also showed that high-volume centers had better outcomes after TP.…”
Section: Introductionmentioning
confidence: 92%
“…6,[12][13][14] However, surgical outcomes and diabetes treatment have improved in recent years. 15,16 For such a preference-sensitive treatment dilemma as total pancreatectomy both the individual and the physician need to be well informed. A shared decision-making approach with decision tables may facilitate this process as it provides a structured and easily accessible evidencebased data overview.…”
Section: Introductionmentioning
confidence: 99%
“…International guidelines currently do not consider prophylactic total pancreatectomy as a treatment option in these patients, due to the relatively high mortality and morbidity associated with this procedure and reduced quality of life due to ‘brittle’ diabetes 6 , 12–14 . However, surgical outcomes and diabetes treatment have improved in recent years 15 , 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation